2012
DOI: 10.1111/jvs.12027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms shaping plant biomass and species richness: plant strategies and litter effect in alkali and loess grasslands

Abstract: Question Explaining the biomass–species richness relationship is key to understanding vegetation dynamics. Several possible mechanisms have been suggested, but complex analysis of plant strategies, major biomass and species richness components along a long productivity gradient is still lacking. We provide a detailed analysis of the relationship between major biomass components (total above‐ground biomass, green biomass and litter), plant strategies and species richness along a long gradient of alkali and loes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 67 publications
7
93
1
20
Order By: Relevance
“…Achilleo-Festucetum had the widest range of vertical position in our study site, likely because this association is characterised by moderate soil fertility and/or moderate salinity, which conditions are likely provided in different elevation zones (Kelemen et al, 2013). Accordingly its species pool includes some generalist species, shared with neighbouring associations, such as Achillea spp.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Achilleo-Festucetum had the widest range of vertical position in our study site, likely because this association is characterised by moderate soil fertility and/or moderate salinity, which conditions are likely provided in different elevation zones (Kelemen et al, 2013). Accordingly its species pool includes some generalist species, shared with neighbouring associations, such as Achillea spp.…”
Section: Discussionmentioning
confidence: 84%
“…Loess grasslands are exposed to drought stress, but not affected by salt-stress and nutrientdeficiency. In contrast alkali steppes are exposed to moderate levels of drought and salt-stress; open alkali swards are exposed to high levels of drought and salinity; while alkali meadows are characterised by no drought and only moderate salt stress Kelemen et al, 2013). Thus, these marked differences in abiotic stress factors -especially topographically controlled soil moisture and salinity (Moeslund et al, 2013a,b) -likely resulted in the clear separation of main vegetation groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found in former studies that species with large seeds can better tolerate the shading effect of litter and can also germinate below thick litter layers . Litter accumulation is typical in the loess grasslands of the region; Kelemen et al (2013) reported amounts of litter ranging between 161-516 g/m 2 . This suggests that large-seeded species can have an establishment advantage compared to small-seeded ones under such conditions (see also Ambika et al 2014).…”
Section: Seed Sowingmentioning
confidence: 99%